2014
DOI: 10.1007/s00125-014-3308-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic predisposition to obesity with type 2 diabetes risk in Han Chinese individuals

Abstract: Aims/hypothesis Obesity is a major risk factor for type 2 diabetes, but little is known about the contribution of BMIassociated loci to type 2 diabetes risk in East Asian populations. Methods In this study, 30 known BMI-associated variants and a genetic risk score (GRS) calculated by summing the BMIincreasing alleles of these variants were tested for associations with type 2 diabetes and related glycaemic traits in 1,873 cases of type 2 diabetes and 1,839 controls in Han Chinese individuals. Logistic and linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Our findings are in line with the results of some previous studies in which the obesity‐risk alleles were associated with IR . In contrast, several studies showed that obesity‐risk alleles were more closely associated with markers of beta cell function than IR in Asian populations . The underlying suggested cause of the discrepancy between other populations was ethnicity, which might reflect the difference in the etiological role of obesity in the development of type 2 diabetes .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are in line with the results of some previous studies in which the obesity‐risk alleles were associated with IR . In contrast, several studies showed that obesity‐risk alleles were more closely associated with markers of beta cell function than IR in Asian populations . The underlying suggested cause of the discrepancy between other populations was ethnicity, which might reflect the difference in the etiological role of obesity in the development of type 2 diabetes .…”
Section: Discussionsupporting
confidence: 91%
“…[3][4][5][6] In contrast, several studies showed that obesity-risk alleles were more closely associated with markers of beta cell function than IR in Asian populations. 16,17 The underlying suggested cause of the discrepancy between other populations was ethnicity, which might reflect the difference in the etiological role of obesity in the development of type 2 diabetes. 17,18 However, in the present study, the Korean population showed that IR had a stronger impact than insulin secretion, suggesting that a genetic susceptibility to obesity may affect IR in the Korean population.…”
Section: Discussionmentioning
confidence: 99%
“…environment seem key factors in the onset and progression of metabolic336 diseases, but obesity and type 2 diabetes are also subject to genetic susceptibility, and risk of 337 OA onset in obese subjects could be affected by common genetic factors128,129 . Since 2007, 338 the single nucleotide polymorphism in the fat mass and obesity-associated (FTO) gene has with risk of excess fat mass and obesity in several populations, so 340 investigating this gene in OA could be of interest130 .…”
mentioning
confidence: 99%
“…On the other hand, the TDT and case‐control analysis suggest that GLIS3 /rs7034200 and VEGFA /rs6905288 are associated with T2D independently of the obesity status. This adiposity independent effect has been reported for other obesity‐associated genetic variants …”
Section: Discussionmentioning
confidence: 99%
“…In addition, some obesity susceptibility loci also increase the risk of T2D independent of body mass index (BMI) or could be mediated by obesity‐predisposing effect . The information about the contribution of obesity‐susceptibility variants to pediatric‐onset T2D is scarce.…”
Section: Introductionmentioning
confidence: 99%